Technology Entrepreneurship Project (ENT 600) : Reece / Muhammad Aiman Saipullah - Saipullah, Muhammad Aiman (2022)
This case study was made to investigate the company and the product that has been made to upgrade it to multi-purpose. It is a part of study for UITM student to undergo a case study project and get an opportunity to know which product that manufactured that can develop for improvement. The company that been choose is Reece company that based in Australia. The Reece company has found drastically increasing the amount of water conservation that occurs across households daily. By reducing water consumption and using a more efficient model uses less energy to treat, pump and heat the water, therefore reducing the amount of greenhouse gas emissions as well. This will further preserve the environment and tackle the demanding issue of climate change. In this report contains specialized subject study. Aim of this project is to study background, organizational structure, products and services that Reece company provides. After that, about the technology that been made and used in their products and how they promote and market it that are quiet interesting. Goals indicate what a business unit wants to achieve. Strategy is an action plan for getting the goals. Every business must design a strategy for achieving its goals, consisting of a marketing strategy, and an effective management. In this case study, we analysed the strength, weaknesses, opportunities and threats of this company in real business world by using SWOT analysis, making it as our innovation to be continued in new Product Development task that can save the water.